2021
DOI: 10.1021/acsomega.0c05844
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment of Polyurethane Foams from Polyols Obtained through Chemical Recycling

Abstract: In this research, the results of the life cycle assessment of polyurethane (PUR) foams with different recycled polyol contents are presented. A methodological framework implementing laboratory activities directly into the life cycle assessment has been developed. Laboratory activities made the primary data related to the recycled polyol production available through the glycolysis of polyurethane scraps and the subsequent production and characterization of the foams. Five different formulations were analyzed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…It turned out that the use of natural waste could therefore be a good solution for waste management [14]. In recent years, there was a growing interest in the application of natural additives in the form of bio-polyol and bio-fillers, especially cellulosic and lignocellulosic raw materials such as nutshells, fruit seeds, coconut fibers, extracts, and others [6,12,[15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…It turned out that the use of natural waste could therefore be a good solution for waste management [14]. In recent years, there was a growing interest in the application of natural additives in the form of bio-polyol and bio-fillers, especially cellulosic and lignocellulosic raw materials such as nutshells, fruit seeds, coconut fibers, extracts, and others [6,12,[15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Fillers of natural and plant origin may also positively affect the mechanical properties of the obtained composites. The literature commonly describes the use of natural additives in polymeric materials [ 8 , 9 , 15 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…A critical analysis of nine chemical recycling LCA papers found that there are two approaches to modeling: a comparison of chemical recycling methods to other plastic waste management techniques, for example, mechanical recycling or the modeling of chemical recycling methods in combination with other plastic waste management methods, to treat mixed plastic waste [ 15 ]. Marson et al presented a life cycle assessment of PUs foams with different recycled polyol contents [ 195 ].…”
Section: Down Stream Problemmentioning
confidence: 99%